If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x(3x + -3) + -6x(7x + -9) = 0 Reorder the terms: 12x(-3 + 3x) + -6x(7x + -9) = 0 (-3 * 12x + 3x * 12x) + -6x(7x + -9) = 0 (-36x + 36x2) + -6x(7x + -9) = 0 Reorder the terms: -36x + 36x2 + -6x(-9 + 7x) = 0 -36x + 36x2 + (-9 * -6x + 7x * -6x) = 0 -36x + 36x2 + (54x + -42x2) = 0 Reorder the terms: -36x + 54x + 36x2 + -42x2 = 0 Combine like terms: -36x + 54x = 18x 18x + 36x2 + -42x2 = 0 Combine like terms: 36x2 + -42x2 = -6x2 18x + -6x2 = 0 Solving 18x + -6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6x'. 6x(3 + -1x) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {0, 3}
| 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 | | 8(y-5)=6-18 | | .20x+.25+9=.21 | | 4-15y=4 | | -14=(2/5)(9-2b) | | -32=(8/7)(3w-1) | | .80x+.25(60)=.70(x+60) | | c=0.90y+1.65 | | 28s-2=59s-64 |